1993
DOI: 10.1103/physrevlett.71.2638
|View full text |Cite
|
Sign up to set email alerts
|

Microwave frequency dependence of integer quantum Hall effect: Evidence for finite-frequency scaling

Abstract: We present ac measurements of the diagonal conductivity o xx , in the integer quantum Hall regime for frequency /between 0.2 and 14 GHz and temperature r>:50 mK. Re(cr xx ) was obtained from the measured attenuation of a coplanar transmission line on the sample surface. For/S; 1 GHz, a xx peaks between IQHE minima broaden as / increases, roughly as (AB) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
162
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(183 citation statements)
references
References 17 publications
20
162
0
1
Order By: Relevance
“…A similar analysis of Dn as a function of frequency has already been performed by Engel et al [10] and Balaban et al [11] with contradicting results concerning the validity of scaling. However, it is important to stress that although the plateau transition is a powerful tool for the test of scaling, it is only an indirect approach to the localization length.…”
Section: High Frequency Conductivity In the Quantum Hall Regimementioning
confidence: 62%
See 1 more Smart Citation
“…A similar analysis of Dn as a function of frequency has already been performed by Engel et al [10] and Balaban et al [11] with contradicting results concerning the validity of scaling. However, it is important to stress that although the plateau transition is a powerful tool for the test of scaling, it is only an indirect approach to the localization length.…”
Section: High Frequency Conductivity In the Quantum Hall Regimementioning
confidence: 62%
“…Previous experiments by Engel et al [10] and Balaban et al [11] were restricted to a measurement of the real part of s xx , whereas our technique gives access to both the real and imaginary part. This allows an additional test of universal frequency scaling.…”
Section: High Frequency Conductivity In the Quantum Hall Regimementioning
confidence: 99%
“…21 . Experiments on the frequency, (f ), dependent conductivity have shown that σ xx peaks broadens as (∆B) ∼ f γ with γ = 0.41 ± 0.04 for the spin split transition and γ = 0.20 ± 0.05 for the spin-degenerate case 25 . This, tantalizing effect was explained in terms of an unstable critical point so that the enhancement of the exponent is understood as an artifact of crossover phenomena 27 (See Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This work is motivated by recent experiments hinting at changes in localization properties when two different Landau levels are nearly degenerate [22][23][24][25][27][28][29] , by growing interest in the conditions necessary for the occurrence of the quantum Hall effect in three-dimensional electron systems, and by the need for improved understanding of the disappearance of the quantum Hall effect at weak magnetic fields in high mobility samples. In each case, we believe that double-layer quantum Hall systems offer advantages for both theoretical studies and for the experimental studies which we hope to motivate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation